2015
DOI: 10.1371/journal.pone.0126527
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Expression of Foxl2 in Pituitary Gonadotropes Requires Ovarian Hormones

Abstract: Gonadotropin-releasing hormone (GnRH) and activin regulate synthesis of FSH and ultimately fertility. Recent in vivo studies cast SMAD4 and FOXL2 as master transcriptional mediators of activin signaling that act together and independently of GnRH to regulate Fshb gene expression and female fertility. Ovarian hormones regulate GnRH and its receptor (GNRHR) through negative and positive feedback loops. In contrast, the role of ovarian hormones in regulating activin, activin receptors, and components of the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…In addition, Neat1 knockout mice fail to become pregnant despite normal ovulation [ 49 ]. Ovarian hormones can regulate the expression of Foxl2 to expand the number of genes controlled by the hypothalamic–pituitary–gonadal axis, ultimately dictating reproductive fitness [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Neat1 knockout mice fail to become pregnant despite normal ovulation [ 49 ]. Ovarian hormones can regulate the expression of Foxl2 to expand the number of genes controlled by the hypothalamic–pituitary–gonadal axis, ultimately dictating reproductive fitness [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Boulanger promised that Forkhead box L2 ( Foxl2 ) loss of function dissociated from loss of lncRNA expression is sufficient to cause an XX female-to-male sex reversal in the goat model and, as in the mouse model, an agenesis of eyelids [ 15 ]. Ovarian hormones regulate Foxl2 expression and thereby expand the number of genes controlled by the hypothalamic–pituitary–gonad axis that ultimately dictates reproductive fitness [ 16 ]. Although lncRNA studies have been begun in several species, the research conducted into the effects of lncRNA on the reproductive rate was relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Nakagawa et al () reported that Neat1 knock‐out mice failed to conceive despite normal ovulation. Ovarian hormones can regulate Foxl2 expression to increase the number of genes controlled by the hypothalamic–pituitary–gonadal axis, eventually dictating reproductive fitness (Herndon & Nilson, ).…”
Section: Discussionmentioning
confidence: 99%
“…The HIRA expression in ovary, oviduct and uterus of low fecundity Sunite sheep was higher than those in high fecundity Small Tail Han sheep indicated that the expression of HIRA may negatively regulate the function of these organs which were especially important for mammal reproduction. Further, it was reported that the hypothalamic-pituitary-gonadal axis (HPG) is the most important system controlling the secretion of the sex hormones gonadotropin-releasing hormone (GnRH), follicle-stimulating hormone (FSH) and luteinizing hormone (LH) in mammals [ 43 , 44 ]. GnRH, FSH and LH are the most important reproductive hormones controlling the reproductive activities of mammals.…”
Section: Discussionmentioning
confidence: 99%